Distribution of mRNA and binding sites of adrenoceptors and muscarinic receptors in the rat heart - Myslivecek, Jaromír; Nováková, Martina; Palkovits, Miklós; Krizanová, Ol'ga; Kvetnanský, Richard (Life sciences, 2006)
Since there exist some obscurities in the expression of mRNAs and their receptors in the heart, we have investigated the gene expression (mRNA levels) of adrenoceptors (alpha1A-, alpha1B-, beta1-, beta2-, beta3-) and muscarinic receptors (M2) and the density of receptor binding sites (alpha1A-, alpha1B-, beta1-, beta2-adrenoceptors, muscarinic receptors). Moreover, the heart regions consist of tissue rich in ganglion cells (that are of importance in heart neural circuits) and those virtually free of them (myocytes). Therefore, we have examined the differences in the distribution of mRNAs/receptor binding sites in the atrial samples of the heart rich in ganglion cells vs. those are virtually free of them. Binding sites and mRNAs of muscarinic receptors and alpha1B-adrenoceptors differ in their distribution in different heart regions. The mRNAs for beta1- and beta2-adrenoceptors were almost equally distributed herein, while the amount of beta-adrenoceptors significantly differs in the heart regions. The alpha1A- and beta3-adrenoceptors mRNAs were also found in all investigated heart regions, but at significantly lower level and have not shown region differences. This is a new finding, especially to beta3-adrenoceptors, as they were not regularly found in each heart regions. alpha1B-adrenoceptors have similar distribution of their mRNAs and binding sites in some heart parts. Thus, we can conclude that there are noticeable differences in the presence of receptors in heart regions that contain ganglion cells in comparison to those are virtually free of them.
Keywords: messenger RNA; Rats; Receptors, Adrenergic; Heart Atria; potkani Sprague-Dawley; Ganglia; mužské pohlaví; receptory muskarinové; srdeční komory; krysa rodu Rattus; srdeční síně; polymerázová řetězová reakce s reverzní transkripcí; Receptors, Muscarinic; Radioligand Assay; myokard; ganglia; zvířata; RNA, Messenger; Binding Sites; Myocardium; Heart Ventricles; Rats, Sprague-Dawley; Reverse Transcriptase Polymerase Chain Reaction; radioligandová zkouška; adrenergní receptory; vazebná místa; Male; Animals